Análise comparativa dos custos e benefícios do escoamento de grãos pelo arco norte em relação aos portos do sul e sudeste - CÂMARA, Thiago Guimarães. (2024)
The present work carries out a comparative analysis of the costs and benefits of grain flow through Arco Norte in relation to ports in the South and Southeast, considering aspects of port infrastructure and logistics, operational and tax costs, and future perspectives. To do so, it uses a literature review methodology based on secondary data and estimated calculations of the total costs of transporting grains along the two routes. The results obtained indicate that Arco Norte is more economically advantageous than the South/Southeast, but requires investments in logistical infrastructure to guarantee the efficiency, safety and competitiveness of grain flow. The work also presents recommendations for improving grain flow through the North Arco and the South/Southeast, aiming to promote integrated and sustainable management of natural resources and production chains.